Embracing ambiguity: Agile insights for sustainability in engineering in traditional higher education and in technical and vocational education and training. Issue 2 (17th June 2019) - Towey, Dave; Walker, James; Ng, Ricky
Abstract : Purpose: Embracing reflective practice and retrospection, with a goal of identifying commonalities, this paper aims to examine delivery of engineering subjects in both traditional higher education (THE) and technical and vocational education and training (TVET). Design/methodology/approach: Reflections on actions and autoethnography were used to examine the teaching and learning experiences of three educators across two higher education (HE) institutions (HEIs) in the greater Chinese context. Literature reviews and historical contexts are outlined to support the approaches and insights identified. Findings: This paper presents a number of common characteristics and challenges identified across both THE and TVET. Drawing on the successful embrace of ambiguity and change in recent software engineering (SE) development paradigms, recommendations are made for how the agile SE themes can be applied in a larger sense to address the wider challenges facing both THE and TVET. Originality/value: To the best of the authors' knowledge, this is the first time that engineering education has been examined and contrasted in the contexts of THE and TVET. The similarities and common challenges may represent a new focus for related work, and the presented insights, from agile methodologies in SE, represent a new perspective for viewing future HE and TVET sustainability.